Modelling of Water-Assisted Flame Synthesis of Carbon Nanotube using Counterflow Diffusion - Muhammad ‘Abid Ira, Irawan; Mohd Fairus, Mohd Yasin; Khairul Fikri, Tamrin (Akademia Baru, 2020)
Research on carbon nanotubes (CNTs) has been performed extensively. On top of that, water-assisted synthesis of CNT has started to emerge with captivating effect towards growth of CNT. The present study investigates a baseline inlet condition for water assisted case utilizing diffusion flame that imitates the temperature distribution and growth region of CNT without water vapor, on the basis of experimental data of non-water assisted high yield CNTs. To affirm the effect of water vapor, 35% to 70% of water vapor has been added replacing the fuel side nitrogen content. The results prove that water vapor suppresses the flame where the maximum temperature drops with increasing concentration. Consequently, this affects the length and growth region of CNTs. The region width has been reduced for about 7.4% to 18.5% with water vapor. This shows that excessive water poorly affects the growth of CNTs. On the other hand, the region has also shifted for about 0.64 mm to the fuel side (5.7%) from the origin when 70% of water vapor was added. Following this, the impact of catalyst towards CNT growth is subsequently presented whereby a comparison is made between Fe and Co to synthesize CNT using flame synthesis. Based on the result, Fe possess better activation for the CNTs to grow as compared to Co. A significant difference between the predicted CNT length for Fe (147 μm) and Co (56 μm) is attributed to their diffusivity values.